Electron delocalization in a 2D Mott insulator - Cosme G. Ayani; Michele Pisarra; Iván M. Ibarburu; Clara Rebanal; Manuela Garnica; Fabián Calleja; Fernando Martín; Amadeo L. Vázquez de Parga (Nature Communications)
Abstract The prominent role of electron-electron interactions in two-dimensional (2D) materials is at the origin of a great variety of fermionic correlated states reported in the literature. Artificial van der Waals heterostructures comprising single layers of highly correlated insulators allow one to explore the effect of the subtle interlayer interaction in the way electrons interact. We study the temperature dependence of the electronic properties of a van der Waals heterostructure composed of a single-layer Mott insulator lying on a metallic substrate by performing quasi-particle interference (QPI) maps. We show the emergence of a Fermi contour in the 2D Mott insulator at temperatures below 11K, which we attribute to the delocalization of the Mott electrons associated with the formation of a quantum coherent Kondo lattice. The comparison between experiments and Density Functional Theory calculations provides a complete picture of the delocalization of the highly correlated electrons from the 2D Mott insulator.